Rheological properties of inverse emulsions stabilized by ethanolamides of tall oil fatty acids; MATEC Web of Conferences; Vol. 85 : Chemistry and Chemical Technology in XXI Century (CCT 2016) - Yanovsky V. A.; Andropov M. O.; Fakhrislamova R. S.; Churkin R. A.; Minaev K. M. Konstantin Madestovich; Ulyanova O. S. Oksana Sergeevna (2016, 2016)
Title screen